2006
DOI: 10.3171/jns.2006.104.6.899
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical treatment with somatostatin analogs in patients with acromegaly: effects on the remission and complication rates

Abstract: At present, the routine use of presurgical therapy with somatostatin analogs for patients with acromegaly cannot be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 35 publications
3
28
1
Order By: Relevance
“…Presurgical SSA administration has been reported to improve surgical outcome and reduce complications (Annamalai et al 2013), but these findings were not confirmed by other authors (Losa et al 2006). Randomised controlled studies exploring the potential benefits are scarce (Carlsen et al 2008, Shen et al 2010, Fougner et al 2014.…”
Section: Surgerycontrasting
confidence: 41%
“…Presurgical SSA administration has been reported to improve surgical outcome and reduce complications (Annamalai et al 2013), but these findings were not confirmed by other authors (Losa et al 2006). Randomised controlled studies exploring the potential benefits are scarce (Carlsen et al 2008, Shen et al 2010, Fougner et al 2014.…”
Section: Surgerycontrasting
confidence: 41%
“…On the other hand, low resection rates of the invasive macroadenomas are reported [5,24]. As indicated by several reports, presurgical long-acting octreotide decreases tumor volume [15,16,[25][26][27][28][29], and so presurgical long-acting octreotide should have greater therapeutic value, if the drug relieves the macroade- resolve this important management question for acromegaly.…”
Section: Discussionmentioning
confidence: 99%
“…Shen and coworkers reported that pre-surgical treatment of invasive macroadenomas with octreotide LAR increased total resection rates and short-term remission rates (both GH and IGF-1 normalized) vs no pre-treatment; however, remission rates during long-term follow-up of the pre-treated group showed no advantage (Shen et al 2010). A retrospective analysis of 286 patients revealed that surgical remission rates were not significantly different whether octreotide or lanreotide was given pre-operatively or not (Losa et al 2006). A recent meta-analysis suggested a statistically significant effect of pre-operative medical therapy on surgical outcome when three prospective controlled trials were analysed, with a pooled odds ratio for biochemical cure with somatostatin analogue pre-treatment of 3.62 (95% CI: 1.88-6.96) (Pita-Gutierrez et al 2013).…”
Section: Clinical Utility As First-line Therapymentioning
confidence: 99%